Development and Validation of a Prognostic Classifier Based on Lipid Metabolism-Related Genes for Breast Cancer [Corrigendum] - Wang N; Gu Y; Li L; Chi J; Liu X; Xiong Y; Zhong C (Journal of Inflammation Research, 2022)
Wang N, Gu Y, Li L, et al. J Inflamm Res. 2022;15:3477–3499. The authors have advised due to an error that occurred inadvertently at the time of figure assembly, the scratch test result of si-SDC1 MBA-MD-231 cells were wrongly placed in the position of the scratch test results of si-SORBS1 MCF-7 cells and therefore, figure part 8F is incorrect. The correct Figure 8 is shown below.